The Influence of Physical Exercise on College Students' Learning Stress and Mental Health - Liang Qi, (Revista de Psicología del Deporte (Journal of Sport Psychology), 2023)
Physical education holds significant value within the higher education system. Sports have the potential to enhance students' physical well-being and foster their self-assurance and resilience. To enhance the athletic abilities of college students and foster their mental well-being, measures need to be taken. The study involved a group of five university students situated in a specific location. A study was conducted with a sample of 700 university students. We distributed a total of 700 questionnaires to students in all three grades for this survey. In total, 658 questionnaires were collected, and 28 invalid questionnaires were excluded due to incomplete, repeated, or continuous answers. Ultimately, a total of 630 valid questionnaires were collected, with a commendable recovery rate of 90%. The competitive learning pressure of the training group was found to be significantly lower than that of the non-training group (t (1, 39) = 45.40, <0.001). Similarly, the frustration learning pressure of the training group was also significantly lower than that of the non-training group (t (1,39) =- 32.80, <0.001). Additionally, the task-required learning pressure of the training group was observed to be significantly lower than that of the non-training group (t(1,39)=-45.79,<0.001). Lastly, the expected learning pressure of the training group was significantly lower than that of the non-training group (t (1,39) =-54.47, <0.001), the self-development learning pressure of the training group was found to be significantly lower than that of the non-training group (t (1, 39) = 21.30, p<0.001). College students can reduce their academic stress by participating in sports training. The students who engaged in sports training experienced a significant decrease in various types of learning pressure, including competitive, frustration, task requirement, expected, and self-development learning pressure, compared to their peers who did not participate in sports training.